Infectious Properties of Avian Influenza A/H5N1 Virus Strains Studied by means of Experiments on Mice - A. A. Sergeev; O. V. P`yankov; O. K. Demina; O. G. P`yankova; E. I. Ryabchikova; A. P. Agafonov; A. N. Sergeev (Проблемы особо опасных инфекций, 2011)
The studied strains of avian influenza virus A/H5N1 (AIV), isolated in the territory of the Russian Federation and CIS countries, can be classified into three groups according to their virulence for mice after intranasal and aerosol challenging: highly virulent strains [50 % aerosol lethal dose (ALD50) - 4,5 lg EID50] - A/Turkey/Suzdalka/Nov-1/2005 and A/Chicken/Suzdalka/Nov-11/2005. Registered is the high degree of correlation (r = 0,89 ) between the indexes of virulence of the strains, obtained by means of intranasal and aerosol challenging of mice. The primary target-cells in mice, respiratory-infected by AIV, are the respiratory tract ciliated cells and pneumonocytes of I, II types.